The Implementation Of Management Functions In Extracurricular Activities To Achieve The Institutional Goals Of MIS Al-Quba Medan - Chair, Sultan Ayughi; Nasution, Inom; Rohman, Fatkhur (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
The management of extracurricular activities plays a strategic role in supporting the achievement of educational institutions' goals, but the implementation of management functions often faces various obstacles that hinder its effectiveness. This study aims to describe the implementation of management functions in extracurricular activities at MIS Al-Quba Medan and identify the obstacles and solutions applied. The research approach uses a descriptive qualitative method with data collection techniques through observation, interviews, and document analysis. The results of the study indicate that management functions are implemented through systematic planning, effective organization, targeted implementation, and routine evaluation. The obstacles faced include a lack of parental support, low student discipline, and a weak administrative system. Solutions were implemented through open communication with parents, motivation- and discipline-based mentoring, strengthening the administrative system, enhancing the capacity of mentors, integrating programs with the institution's vision, and strengthening internal and external synergies. These findings emphasize that the consistent and adaptive application of management functions can enhance the effectiveness of extracurricular activities and support the achievement of educational goals in a sustainable manner.